Photodegradation and ecotoxicology of acyclovir in water under UV254 and UV254/H2O2 processes. (1st October 2017) - Russo, Danilo; Siciliano, Antonietta; Guida, Marco; Galdiero, Emilia; Amoresano, Angela; Andreozzi, Roberto; Reis, Nuno M.; Li Puma, Gianluca; Marotta, Raffaele
Abstract: The photochemical and ecotoxicological fate of acyclovir (ACY) through UV254 direct photolysis and in the presence of hydroxyl radicals (UV254 /H2 O2 process) were investigated in a microcapillary film (MCF) array photoreactor, which provided ultrarapid and accurate photochemical reaction kinetics. The UVC phototransformation of ACY was found to be unaffected by pH in the range from 4.5 to 8.0 and resembled an apparent autocatalytic reaction. The proposed mechanism included the formation of a photochemical intermediate ( ϕ ACY = (1.62 ± 0.07)·10 −3 mol ein −1 ) that further reacted with ACY to form by-products ( k' = (5.64 ± 0.03)·10 −3 M −1 s −1 ). The photolysis of ACY in the presence of hydrogen peroxide accelerated the removal of ACY as a result of formation of hydroxyl radicals. The kinetic constant for the reaction of OH radicals with ACY ( k OH/ACY ) determined with the kinetic modeling method was (1.23 ± 0.07)·10 9 M −1 s −1 and with the competition kinetics method was (2.30 ± 0.11)·10 9 M −1 s −1 with competition kinetics. The acute and chronic effects of the treated aqueous mixtures on different living organisms ( Vibrio fischeri, Raphidocelis subcapitata, D. magna ) revealed significantly lower toxicity for the samples treated with UV254 /H2 O2 in comparison to those collected during UV254 treatment. This result suggests that the addition of moderate quantity of hydrogen peroxide (30–150 mg L −1 ) might be a useful strategy to reduce the ecotoxicity of UV254 based sanitary engineered systems for water reclamation. Graphical abstract: Highlights: Photolysis and UV/H2 O2 degradation of acyclovir were studied in a microphotoreactor UV254 photolysis quantum yield of acyclovir was estimated (1.62·10 −3 mol ein −1 ). Kinetic constant of hydroxyl radical attack to acyclovir was evaluated. H2 O2 assisted photo-oxidation process reduces the ecotoxicity of acyclovir.